Patrón de presentación de apendicitis en el hospital Isidro Ayora en el periodo 2011 2015 de la ciudad de Loja - Córdova Lalangui, Jefferson Leonel (2018)
Abstract: The purpose of this research is to determine the pattern of presentation of appendicitis in the Hospital Isidro Ayora, taking into account the age and sex of patients, the phase of appendicitis and post-surgical complications. A descriptive and retrospective study was carried out, consisting of a sample of 274 clinical records of patients seen at the Hospital of Isidro Ayora de Loja with post-surgical diagnosis of appendicitis in the period 2011 to 2015; the data obtained were entered in the program Excel 2005 and later analyzed in the program IBM SPSS Statistics 24. It was observed that 58.03% were male; the prevailing age group was between 16 - 20 years old with 21.50%; Phlegmonous phase II in 42.70% and postoperative complications occurred in 2.19% (6 cases). In conclusion, these data are similar to those recorded in the universal literature; therefore, there is no change in the pattern of presentation of appendicitis in the patients treated at that hospital.